2019
DOI: 10.1016/j.psychsport.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Do fluctuations in positive affective and physical feeling states predict physical activity and sedentary time?

Abstract: Objectives-Higher levels of positive affect and feelings of energy and vitality are associated with greater physical activity (PA) and lower sedentary time (ST). However, whether fluctuations in these feelings contribute to the regulation of these behaviors is unclear. This study examined the extent to which within-person variability in positive affect and feeling energetic predicted participants' overall levels of PA and ST. Design-This analysis combined data from four ecological momentary assessment (EMA) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
(47 reference statements)
1
21
1
Order By: Relevance
“…In line with the present results, a previous finding from Schwerdtfeger et al 11 shows that increased affect ratings were associated with lower amounts of sedentary behavior. Contrary to our results, Maher et al 12 did not find a within‐subject association between positive affect and feelings of energy. There might be several possible explanations for this inconclusive state of research.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In line with the present results, a previous finding from Schwerdtfeger et al 11 shows that increased affect ratings were associated with lower amounts of sedentary behavior. Contrary to our results, Maher et al 12 did not find a within‐subject association between positive affect and feelings of energy. There might be several possible explanations for this inconclusive state of research.…”
Section: Discussioncontrasting
confidence: 99%
“…Schwerdtfeger et al 11 examined the relationship between affective states and physical behavior in daily life, with the result that affect is inversely associated with sedentary periods, suggesting that both positive and negative affective states are associated with a decrease in sedentary activities. Moreover, Maher and researchers 12 investigated the extent to which within‐subject variability in positive affect and feelings of energy predicted sedentary time. This study did not reveal any association between within‐subject variability in affect or energy and sedentary time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent study across 661 participants aged 8-73 years found that people with higher fluctuations in perceived subjective energy showed less physical activity. From this, the authors concluded that instability in emotional states may either deplete self-regulatory capabilities for physical activity planning or that physical activity can stabilize emotional states [74]. Another common symptom in BPD is unbearable inner tension, which patients sometimes can only manage by engaging in non-suicidal self-injury, substance abuse, or other ultimately maladaptive behaviors.…”
Section: Implications For Bpdmentioning
confidence: 99%
“…What the theory does not include is the possibility for oscillations between states and the impact of this on coping effectiveness and long-term distress. Many psychological factors including distress fluctuate daily ( Kukk and Akkermann, 2017 ; Pihet et al, 2017 ; Maher et al, 2019 ). Thus, future studies that utilize different non-linear analytic techniques are needed to refine the multiple shift question in trauma adaptation.…”
Section: Discussionmentioning
confidence: 99%